Statistical analysis of dynamic experimental data from compression and tensile hopkinson bars - Lim, Leroy Boon Peng. (2011)
The extensive studies of metal alloys in the engineering industry provide us with a wide range of metal selection for our applications and design. Different combination of the metal element will result in different physical and mechanical properties of the metal alloys. The Split Hopkinson Pressure Bar (SHPB) is a frequently used technique to examine the materials and provide a better understanding of the materials‟ behavior when subject to dynamic loading. The material will exhibit a different stress-strain behavior from that under static loading and the main emphasis is to discover the behavior of initial kinetic energy in a specimen. As it is known, the results obtained from experiments conducted in the laboratory are always different to a certain degree of accuracy even though they are repeated many times under same operating conditions. In the case of the SHPB tests, the handling of strain gauges and the oscilloscope are crucial to obtain accurate results. Calibration on the equipments and apparatus setup will also help improve accuracy. However, researchers have a problem in determining the correct value from a set of data collected from repeated experiments due to the variability. This project aims to gather, analyze and make inferences and also apply different statistical analysis methods on these sets of data to obtain more accurate results.